2017
DOI: 10.1038/nsmb.3372
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of Mcm2–7 replicative helicase loading by ORC–Cdc6 and Cdt1

Abstract: To start DNA replication, the Origin Recognition Complex (ORC) and Cdc6 load a Mcm2-7 double hexamer onto DNA. Without ATP hydrolysis, ORC-Cdc6 recruits one Cdt1-bound Mcm2-7 hexamer, forming an ORC-Cdc6-Cdt1-Mcm2-7 (OCCM) helicase loading intermediate. Here we report a 3.9Å structure of the OCCM on DNA. Flexible Mcm2-7 winged-helix domains (WHD) engage ORC-Cdc6. A three-domain Cdt1 configuration embraces Mcm2, Mcm4, and Mcm6, nearly half of the hexamer. The Cdt1 C-terminal domain extends to the Mcm6 WHD, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
269
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 150 publications
(304 citation statements)
references
References 72 publications
(142 reference statements)
20
269
2
1
Order By: Relevance
“…Unlike other Orc/Cdc6 proteins, Orc4 appears responsible for sequence-specific DNA interactions in the OCCM, as it uniquely makes base-specific contacts in the major groove of the DNA ( Fig. 2D; Yuan et al 2017). However, the functional relevance of these interactions is still outstanding.…”
Section: Origin Recognitionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike other Orc/Cdc6 proteins, Orc4 appears responsible for sequence-specific DNA interactions in the OCCM, as it uniquely makes base-specific contacts in the major groove of the DNA ( Fig. 2D; Yuan et al 2017). However, the functional relevance of these interactions is still outstanding.…”
Section: Origin Recognitionmentioning
confidence: 99%
“…Orc1-5, but not Orc6, have a conserved protein structure consisting of one N-terminal AAA + domain and one C-terminal winged helix domain (WHD) ( Fig. 2A; Bleichert et al 2015;Tocilj et al 2017;Yuan et al 2017). Structural analysis showed that H. sapiens Orc6 has homology with transcription factor TFIIB (Liu et al 2011).…”
Section: Origin Recognitionmentioning
confidence: 99%
See 3 more Smart Citations